AUDITORS’ ROLE IN FINANCIAL STATEMENT FRAUD PREVENTION AND REPORTING QUALITY IN NIGERIAN NOT FOR-PROFIT ORGANIZATIONS: EVIDENCE FROM NATIONAL AGENCY FOR THE CONTROL OF AIDS (NACA) - Gabriel, Femi Goodwill; Oricha, Shuaibu Hamzah; Ademu, Sylvester Onyekachi (Kashere Journal of Management Sciences, 2025)
This study investigates the role of auditors in financial Statement fraud prevention in not for profit organization in Nigeria: by taking audit assertions and evidence to enhance financial reporting quality , using the National Agency for the Control of AIDS (NACA) as a case study. The research examined how auditors’ compliance with international audit standards, audit planning and execution, and risk assessment/internal control systems influence three key dimensions of financial reporting quality: relevance, faithful representation, and comparability. The study adopted a descriptive survey design and employed a purposive sampling technique to gather data from 70 audit and finance professionals affiliated with NACA. A structured questionnaire was used to collect primary data, which was analyzed using SPSS for reliability testing and E-Views for regression analysis. The Ordinary Least Squares (OLS) results revealed that each auditor role had a statistically significant positive effect on its corresponding reporting quality dimension. Specifically, compliance with audit standards enhanced relevance, audit planning improved faithful representation, and risk assessment strengthened comparability. The findings underscore the strategic importance of auditors not only in preventing fraud but also in promoting the credibility and usefulness of financial information in non- profit organizations by taking audit assertions and evidence to enhance financial reporting quality. The study contributes to literature by contextualizing audit practices within a donor-funded Nigerian agency, and it recommends stronger adherence to international standards, risk-based audit approaches, and capacity development for non -profit organisation focused auditors.